2015
DOI: 10.1007/s00209-015-1545-1
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial restrictions on the tree class of the Auslander–Reiten quiver of a triangulated category

Abstract: Abstract. We show that if a connected, Hom-finite, Krull-Schmidt triangulated category has an Auslander-Reiten quiver component with Dynkin tree class then the category has Auslander-Reiten triangles and that component is the entire quiver. This is an analogue for triangulated categories of a theorem of Auslander, and extends a previous result of Scherotzke. We also show that if there is a quiver component with extended Dynkin tree class, then other components must also have extended Dynkin class or one of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is a triangulated analogue of [13,Proposition 2.8]. Note that our proof of (1) part b) is much the same as the proof of [7,Lemma 2.2]. Observe also that (2) follows from [16, Proposition 3.1] in the case where R is an algebraically closed field, and that the argument generalizes to our context.…”
Section: A -R Gmentioning
confidence: 55%
See 1 more Smart Citation
“…It is a triangulated analogue of [13,Proposition 2.8]. Note that our proof of (1) part b) is much the same as the proof of [7,Lemma 2.2]. Observe also that (2) follows from [16, Proposition 3.1] in the case where R is an algebraically closed field, and that the argument generalizes to our context.…”
Section: A -R Gmentioning
confidence: 55%
“…Reiten and van den Bergh showed that a Hom-finite Krull-Schmidt triangulated category has AR-triangles if and only if it admits a Serre functor [15]. More recently, Diveris, Purin and Webb proved that if a category as above is connected and has a stable component of the Auslander-Reiten quiver of Dynkin tree class, then this implies existence of AR-triangles [7].…”
mentioning
confidence: 99%
“…The lemmas below, which yield a triangulated analogue of [15,Proposition 2.8], provide an important step in the proofs of Theorem 2.4 and Theorem 2.5. Note that parts of our proof of Lemma 2.2 is much the same as the proof of [8,Lemma 2.2]. Observe also that Lemma 2.3 follows from [19,Proposition 3.1] in the case where R is an algebraically closed field, and that the argument generalizes to our context.…”
Section: Recall From [12] That a Distinguished Trianglementioning
confidence: 63%
“…Reiten and van den Bergh showed that a Hom-finite Krull-Schmidt triangulated category has AR-triangles if and only if it admits a Serre functor [18]. More recently, Diveris, Purin and Webb proved that if a category as above is connected and has a stable component of the Auslander-Reiten quiver of Dynkin tree class, then this implies existence of AR-triangles [8].…”
Section: Introductionmentioning
confidence: 99%
“…Evidently the long exact sequence becomes the three-term sequence shown. This lemma has many consequences: one application of it is described in [6]. The rest of this paper is devoted to studying its implications for bilinear forms on Grothendieck groups.…”
Section: The Basic Lemmamentioning
confidence: 99%